The pattern and translation of Chinese address terms in contemporary film Happiness Around the Corner - Chunli, Yu; Mansor, Nor Shahila; Ang, Lay Hoon; Sharmini, Sharon (Sciedu Press, 2022)
This paper discusses the translation and classification of Chinese address terms by selecting a representative film with a range of contexts. The data for this study were collected from a Chinese comedy film Happiness Around the Corner screened in 2018 with a length of 91.34 minutes. This film was chosen firstly because it was highly rated by the Chinese mainstream media People’s Daily Overseas Edition for its conveying of positive energy in a humorous manner. Furthermore, considering a range of contexts and interlocutors in this film, the data collected from this film would be sufficient to reach the expected goals of the study. This study employs a qualitative approach to explore a proper classification of Chinese contemporary address terms. The Chinese address terms found in the selected film were classified into seven types: namely nickname, professional title, kinship terms, fictive kinship terms, professional title with surname, offensive address terms and full name. The findings show that professional title, nickname and kinship terms appeared with higher frequency than offensive address terms and full name in this film, which could be explained from the perspective of sociolinguistics. Literal plus liberal translation strategies are recommended to translate address terms using homophonic puns, and equivalent words in target language are advised in most cases. These findings could not only throw light on the classification of address terms in Chinese, but also promote translation studies.